PERANCANGAN DAN IMPLEMENTASI DASHBOARD TAGIHAN PADA PENGGUNAAN LAYANAN CLOUD - Berlin P Sitorus; Lukman Bahar Agung Pambudi; Rivan Nauval; Arqi Falah (JURNAL SATYA INFORMATIKA, 2026)
The utilization of cloud computing services has significantly increased to support organizational information technology infrastructure. However, the complexity of cloud service billing models often creates challenges in cost monitoring and resource usage transparency. This research aims to design and implement a billing dashboard for cloud service usage to improve cost visibility, billing calculation accuracy, and role-based access management. The software development method used is Waterfall with Unified Modeling Language (UML) modeling. System testing was conducted using White Box Testing and User Acceptance Test (UAT). The results indicate that the developed system is capable of presenting billing information transparently and accurately while supporting effective cloud cost management decision-making.